Improving SLM additive manufacturing operation precision with H-infinity controller structure. (May 2021) - Rasoanarivo, Fetra; Dumur, Didier; Rodriguez-Ayerbe, Pedro
Abstract: SLM (Selective Laser Melting) is the most widespread additive manufacturing technique of metal part. The desired part is elaborated through local melting of a raw metal powder bed by means of laser. In industrial machines, galvanometer motors achieve the laser beam deflection and focus control tasks. This paper proposes a H-infinity controller synthesis which improves the system accuracy and robustness towards physical features. Compared to a conventional control scheme, results obtained with the H-infinity controller implemented in an open architecture test bench consisting of a 2-axis laser deflection system showed improved accuracy performance while operation rapidity is optimized.